The performance of a pilot-scale anaerobic hybrid bioreactor on palm oil mill effluent treatment - Adrianto Ahmad; Bahruddin Bahruddin; David Andrio; Amir Hamzah (Dept. of Chemical Engineering, Diponegoro University, 2019)
Contemporarily, Indonesia and Malaysia are the largest contributors of crude palm oil (CPO) in the world by up to 40%, and 37.3%, respectively. Furthermore, its production value this year reached 19.7 million tons, where each generates 2.5 m3 of wastewater. Meanwhile, of all the provinces in Indonesia specifically, Riau is the largest supplier for exports by up to 38%, generated from 225 palm oil mills, where a total of 6.3 million tons resulting in the generation of about 15.75 million m3 of wastewater, with organic content between the range of 30,000-60,000 mg COD/l. In addition, one of the uses of this wastewater includes anaerobic processes, with the double benefit of reducing COD concentrations, subsequently applying it as fertilizer, and also in the production of methane gas, as an alternative source of energy. The purpose of this study, therefore, is to observe the effect of bioreactor volume, scale-up on the performance of anaerobic hybrid bioreactors, in the treatment of mill effluents. The technology examined in this study was the anaerobic hybrid bioreactor with the dimensions of length 22 m, width 10 m, and depth 1.5 m, and a total volume of 330 m3, which is impermeable to oxygen, and a 250 m3 effective working volume. This was built and operated at a hydraulic retention time of 1 day, in the Palm Oil Mill of Riau, and the results showed the environmental conditions to range from a pH of 7.2 to 8.0, with temperatures from 320C to 350C, acetic acid of 774 mg/l to 1,180 mg/l, and alkalinity of 2,149 mg/l up to 2,400 mg/l. Furthermore, the performance of these reactors are shown by the highest COD removal efficiency of 77.8%, and a biogas test for the propensity of being applied as an alternative energy source obtained a methane gas concentration of 54%. Keywords: anaerobic, bioreactor, biogas, wastewater, performance, palm oil mill effluent